ANALISIS PERHITUNGAN BIAYA BERDASARKAN PROSES (PROCESS COSTING) PADA INDUSTRI KOPI BUBUK CAP 3 HARIMAU AIR RAMBAI CURUP - Meriana (Jurnal Ilmiah Raflesia Akuntansi, 2020)
This research is to know the system of cost calculation based on process of Coffee Powder Industry Cap 3 Tiger Water Rambai Curup in order to control company's finance.The analysis used in this research is quantitative analysis method.The results of this study can be concluded that the Coffee Powder Industry Cap 3 Water Tiger Rambai Curup in calculating the production cost contains about the calculation of production costs for mass products and calculation of production costs for products managed by one department. The deviation is large enough to calculate the cost of the finished product that is transferred to the warehouse and the cost of the product in the process at which the end of the month has not been produced. Irregularities occur because the level of sales is influenced by the costs of production, the time factor to complete per unit and per unit of product, and the advantages and disadvantages of costs and materials in the production of mass products. Control is more effective by using process costing (Process costing).